2010
DOI: 10.1111/j.1365-2982.2010.01556.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic electrical stimulation reduces blood glucose in diabetic rats

Abstract: Hepatic electrical stimulation is capable of reducing both fasting and fed blood glucose in normal, and type 1 and type 2 diabetic rats and the effect may be partially mediated via an increase in GLP-1 release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In contrast, oral sCT, by following the endogenous physiological pathway and thereby resulting in higher drug concentrations in the splanchnic circulation could cause pronounced exposure to receptors and nerves located in the pancreatic and portal area. In support of this hypothesis, stimulation of hepatic vagal afferents resulting in hypothalamic mediated insulin secretion has been demonstrated to improve hyperglycaemia in ZDF rats (Chen et al ., 2010). Additionally, in preliminary experiments, the CT receptor was localized by immunohistochemistry as being dispersed throughout the pancreas islet including beta cells (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, oral sCT, by following the endogenous physiological pathway and thereby resulting in higher drug concentrations in the splanchnic circulation could cause pronounced exposure to receptors and nerves located in the pancreatic and portal area. In support of this hypothesis, stimulation of hepatic vagal afferents resulting in hypothalamic mediated insulin secretion has been demonstrated to improve hyperglycaemia in ZDF rats (Chen et al ., 2010). Additionally, in preliminary experiments, the CT receptor was localized by immunohistochemistry as being dispersed throughout the pancreas islet including beta cells (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…That is, application of a 4-mA, 300-μsec, and 70-msec stimulus, which corresponds to electrical stimulation parameters used in gastric stimulation for the reduction of nausea, results in a significant increase in circulating glucose (explained by a likely attenuation in whole body glucose uptake because of the observed decrease in insulin associated with the stimulus). However, application of a 4-mA, 300-μsec, and 25-msec stimulus, results in a decrease in glucose with an associated increase in circulating insulin (Chen et al 2010). While in both instances there is a clear direct effect on hepatic tissues by the electrical stimulus resulting in local changes in glycogenesis and glycogenolysis, it is also clear that the stimulation of the present hepatic vagus nerve alters the secretion of insulin by the pancreas (Rozman et al 2002;Rozman and Bunc 2004).…”
Section: Some Additional Comparisons Of Hepatic Ultrasound To Implant...mentioning
confidence: 99%
“…Intriguingly, a previous study demonstrated that hepatic electrical stimulation decreased fasting and fed blood glucose in normal and diabetic rats, a result that may be mediated by the release of glucagon-like peptide-1 (GLP-1) (33). Moreover, another previous study demonstrated that SGES using optically appropriate parameters improved vagotomy-induced impairment in gastric accommodation resulting from vagotomy (34).…”
Section: Discussionmentioning
confidence: 99%